Application of laser microdissection to identify the mycorrhizal fungi that establish arbuscules inside root cells - Berruti, Andrea; Borriello, Roberto; Lumini, Erica; Scariot, Valentina; Bianciotto, Valeria; Balestrini, Raffaella (Frontiers in Plant Science, 2013)
Obligate symbiotic fungi that form arbuscular mycorrhizae (AMF; belonging to the Glomeromycota phylum) are some of the most important soil microorganisms. AMFs facilitate mineral nutrient uptake from the soil, in exchange for plant-assimilated carbon, and promote water-stress tolerance and resistance to certain diseases. AMFs colonize the root by producing inter- and intracellular hyphae. When the fungus penetrates the inner cortical cells, it produces a complex ramified structure called arbuscule, which is considered the preferential site for nutrient exchange. Direct DNA extraction from the whole root and sequencing of ribosomal gene regions are commonly carried out to investigate intraradical AMF communities. Nevertheless, this protocol cannot discriminate between the AMFs that actively produce arbuscules and those that do not. To solve this issue, the authors have characterized the AMF community of arbusculated cells through a laser microdissection (LMD) approach, combined with sequencing-based taxa identification. The results were then compared with the AMF community that was found from whole root DNA extraction. The AMF communities originating from the LMD samples and the whole root samples differed remarkably. Five taxa were involved in the production of arbuscules, while two taxa were retrieved inside the root but not in the arbusculated cells. Unexpectedly, one taxon was found in the arbusculated cells, but its detection was not possible when extracting from the whole root. Thus, the LMD technique can be considered a powerful tool to obtain more precise knowledge on the symbiotically active intraradical AMF community.